Proline and ions accumulation in four Passiflora species under water-saline stress - Hurtado Salazar, Alejandro; Pereira da Silva, Danielle Fabiola; Ceballos-Aguirre, Nelson; Ocampo, John; Horst Bruckner, Claudio (Comunicata Scientiae, 2018)
Water-saline stress is one of the factors limiting growth and crop production, with the induction of morphological, structural and metabolic changes in higher plants. This study aimed to evaluate the response of four species with ten accessions of Passiflora to saline stress and drought stress, and the accumulation of proline and content of cationic macronutrients and their relationships with sodium. The plants were grown under controlled conditions for seven months, watered with nutrient solution with additions of NaCl (100 mM) to achieve the desired conductivities (1.5, 2.5, 4.0, and 5.5 dS m-1) and constant substrate humidity of 100%, 66% and 33%. The concentrations of Na+, K+, Ca++, Mg++ and proline in the leaves were determined. Proline accumulation increased in salinized plants, especially in young leaves. Proline increase was evident in accessions tolerant and moderately tolerant to salinity. These results indicate that tolerance to salinity and water stress in Passiflora relates to an improved ability to exclude sodium and greater ability to accumulate proline for osmotic adjustment. The increased salinity of the nutrient solution increased sodium contents, relations Na+/Ca++, Na+/Mg++, Na+/K+, and decreased Ca++, Mg++ and K+ levels, reflecting the nutritional imbalance caused by progressive saline stress.